WHAT LAUDATO SÍ MEANS TO MALAWI - Muyebe , Alex; Henriot, Peter (Asian Horizons, 2015)
as one of the poorest countries in the world. It faces serious climatechange problems (floods and droughts) caused by deforestation that is closely linked to its main export earning crop, tobacco. The strong words of Pope Francis’s Laudato Sí, recognising the reality of climate change and its impact on the poor, is very relevant to Malawi. One practical response to curtailing deforestation is the promotion of small clay stoves (mbaula) that do not use charcoal or large amounts of fire wood for cooking purposes. Another response is found in the construction and instruction of the new Jesuit secondary school supporting a “green” (environmentally sensitive) culture.